2000
DOI: 10.1016/s0377-1237(17)30131-4
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Tuberculosis Diagnostic Techniques

Abstract: Tuberculosis is re-emerging as an important cause of morbidity and mortality in man. This article outlines current strategies available for the diagnosis of tuberculosis, and its applicability. Fluorescent staining, modified culture methods, antigen detection, ELISA based assays against various antigen preparation and recent advances in molecular techniques have been outlined. Present strategies being developed at Armed Forces Medical College for the early diagnosis, speciation, antibiotic sensltivlty testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…The sensitivity varies depending on the source of the sample. Sensitivity ranges from 46-78% and the specificity is virtually 100% [37]. Sensitivity and specificity of AFB on aspirate smear from lymph nodes in a study in our department was found to be 76.47% and 100% respectively [34].…”
Section: Necrotic Materials Onlymentioning
confidence: 72%
“…The sensitivity varies depending on the source of the sample. Sensitivity ranges from 46-78% and the specificity is virtually 100% [37]. Sensitivity and specificity of AFB on aspirate smear from lymph nodes in a study in our department was found to be 76.47% and 100% respectively [34].…”
Section: Necrotic Materials Onlymentioning
confidence: 72%
“…•Enzyme Linked Immunosorbent Assay (ELISA) for antigen detection (3) The detection of mycobacterial antigens in sputum, CSF and pleural and ascitic fluids can be done by using double antibody sandwich procedures of ELISA. The tests lack specificity because of the use of polyclonal antibodies.…”
Section: Development Of Interferon Gamma Releasementioning
confidence: 99%
“…Microbiological confirmation currently depends on obtaining an adequate sample for acid fast staining, culture and sensitivity. [2] An outline of tests used for identification of mycobacteria: (3) Mycobacteria are classified as category three pathogens and should be processed in biological safety cabinets ( (3) The identification of tuberculostearic acid (TBSA) in clinical samples is an alternative approach available in gas chromatography. TBSA can be detected by gas chromatography-mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A baciloscopia apresenta como principal desvantagem a sensibilidade limitada, sendo necessários pelo menos 5.000 bacilos por mL de amostra para obter-se um resultado positivo e, além disso, requer habilidade e experiência do microscopista (Menon et al, 2000;Ganguly, 2002;Ramachadran & Paramasivan, 2003).…”
Section: Baciloscopiaunclassified